Adverse bone health among children and adolescents growing up with HIV - Tavitiya Sudjaritruk; Thanyawee Puthanakit (Elsevier, 2015)
Adverse bone health is one of the important non-communicable conditions during the course of life-long HIV treatment. Adolescence is the critical period of bone mineral acquisition for attaining adult peak bone mass. With traditional and HIV-related risk factors, adolescents growing with HIV have a greater chance of having impaired bone mineral density (BMD). Prevalence of low BMD has been reported in 16-32% of HIV-infected adolescents from middle-income countries. The deep interaction between the immune and skeletal systems, called the immunoskeletal interface, is proposed as one of the underlying mechanisms of adverse bone health in HIV-infected individuals. Dual-energy X-ray absorptiometry (DXA) is a standard tool to assess BMD among HIV-infected adolescents. Non-invasive imaging techniques such as quantitative computed tomography (QCT) and quantitative magnetic resonance imaging (QMRI) provide more information on true volumetric density and bone microarchitecture. To date, there are no paediatric recommendations on the treatment and prevention of adverse bone health. Having a healthy lifestyle, routine weight-bearing exercises and adequate dietary intake are the standard approaches to optimise bone health. There are several ongoing randomised clinical trials using pharmacological treatment options, for example vitamin D, calcium and alendronate to improve bone health among this population.